β-Cell Generation: Can Rodent Studies Be Translated to Humans? - Françoise Carlotti; Arnaud Zaldumbide; Johanne H. Ellenbroek; H. Siebe Spijker; Rob C. Hoeben; Eelco J. de Koning (Journal of Transplantation)
β-cell replacement by allogeneic islet transplantation is a promising approach for patients with type 1 diabetes, but the shortage of organ donors requires new sources of β cells. Islet regeneration in vivo and generation of β-cells ex vivo followed by transplantation represent attractive therapeutic alternatives to restore the β-cell mass. In this paper, we discuss different postnatal cell types that have been envisaged as potential sources for future β-cell replacement therapy. The ultimate goal being translation to the clinic, a particular attention is given to the discrepancies between findings from studies performed in rodents (both ex vivo on primary cells and in vivo on animal models), when compared with clinical data and studies performed on human cells.